2018
DOI: 10.1186/s12879-018-3502-1
|View full text |Cite
|
Sign up to set email alerts
|

Genomic sequencing is required for identification of tuberculosis transmission in Hawaii

Abstract: BackgroundTuberculosis (TB) caused an estimated 1.4 million deaths and 10.4 million new cases globally in 2015. TB rates in the United States continue to steadily decline, yet rates in the State of Hawaii are perennially among the highest in the nation due to a continuous influx of immigrants from the Western Pacific and Asia. TB in Hawaii is composed of a unique distribution of genetic lineages, with the Beijing and Manila families of Mycobacterium tuberculosis (Mtb) comprising over two-thirds of TB cases. St… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…All variant-calling pipelines compared here have been applied, formed the basis of, or have been proposed for transmission inference (e.g. pipeline A: [28]; B: [29]; C: [30]; D: [18]) and varied in quality control, choice of reference genome, mapper, caller, variant filters and genomic regions excluded (Table S1, available in the online version of this article).…”
Section: Resultsmentioning
confidence: 99%
“…All variant-calling pipelines compared here have been applied, formed the basis of, or have been proposed for transmission inference (e.g. pipeline A: [28]; B: [29]; C: [30]; D: [18]) and varied in quality control, choice of reference genome, mapper, caller, variant filters and genomic regions excluded (Table S1, available in the online version of this article).…”
Section: Resultsmentioning
confidence: 99%
“…Two schema exist for this approach: 183 the core genome (termed cgMLST; 2891 genes covering 2.86 million bases 31 ) and an extended 184 pan-genome including 1141 accessory loci 11 (termed wgMLST). These WGS-based approaches have been shown to perform better than contact tracing and with higher resolution than classical approaches such as MIRU-VNTR 12,13,30,31,33 . This currently recommended data processing workflow (Fig.…”
mentioning
confidence: 99%
“…Currently, two Mtbc-specific pipelines are available, which perform multiple core tasks in single install set-up to produce genetic variant calls from raw Illumina sequence data (MTBseq 34 and 196 UVP-ReSeqTB 35 ). Other pathogen-agnostic pipelines can be used with an Mtbc-specific 197 reference genome and drug resistance database to achieve similar results 33,[36][37][38] . Numerous 198 custom-built pipelines also exist 8,[39][40][41][42][43][44][45][46] , often incorporating similar tools for mapping and variant calling with additional accessory tools and in-house scripts to parse and refine outputs.…”
mentioning
confidence: 99%
“…MIRU-VNTR typing is widely used to determine relatedness and track transmission dynamics of specific isolates of M. tuberculosis [19]. Because MIRU-VNTR analysis examines only a small proportion of M. tuberculosis genome, this method may have limited resolution [20,21]. Molecular epidemiological study in English Midlands showed MIRU-VNTR typing and epidemiological risk factors are poorly predictive of close genomic relatedness when comparing to WGS, and MIRU-VNTR performance varies markedly by lineage of M. tuberculosis [19].…”
Section: Discussionmentioning
confidence: 99%
“…Molecular epidemiological study in English Midlands showed MIRU-VNTR typing and epidemiological risk factors are poorly predictive of close genomic relatedness when comparing to WGS, and MIRU-VNTR performance varies markedly by lineage of M. tuberculosis [19]. Another study from Hawaii reported 24-loci MIRU-VNTR typing has specificity of 28.6% for identifying actual transmission clusters, and this traditional typing has poor performance especially when identifying transmission in Beijing and Manila family clusters [21]. Contrary to traditional genotyping methods, WGS Provides detailed insights into transmission dynamics [22,23].…”
Section: Discussionmentioning
confidence: 99%